Image of Minangkabau Women in the Kaba Siti Risani - Chintia, Chintia; Nursaid, Nursaid; Suhaili, Samsudin; Ningsih, Ayu Gustia (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to explore: (1) The physical and psychological representation of Minangkabau women in the kaba "Siti Risani" by Sutan Nasarudin, (2) The role of Minangkabau women in the family context in the kaba, (3) The role of Minangkabau women in the context of society in the kaba "Siti Risani." The research method used is qualitative with a descriptive approach, using the book "Siti Risani" by Sutan Nasarudin as a data source. The data collection steps involved understanding the image of Minangkabau women, literature study, character identification, and data recording. Triangulation techniques were used to validate the data. The research results reveal two aspects of the image of Minangkabau women, namely physical and psychological. Physical image is divided into women who emphasize beauty and gentleness, and those who show strength and grace. Psychic image involves five aspects, including firmness, good manners, steadfastness, discipline, perseverance, patience, and compassion. The role of Minangkabau women in the family includes three main roles, namely as wife, mother and family member. The role of Minangkabau women in society is divided into two, namely as Limpapeh Rumah Gadang and Bundo Kanduang. The keywords of this research include image, Kaba, and women